2004
DOI: 10.1103/physrevlett.93.076103
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth on a Superhydrophobic Grooved Surface

Abstract: The growth dynamics of water drops condensed on a superhydrophobic geometrically patterned surface were studied. Drop size evolution at early and intermediate times is self-similar. Drop growth laws do not differ for a flat surface because of a reduction of both drop and substrate dimensionality. A striking observation is the instantaneous drying of the top surface of grooves at a point in time due to coalescence of the drops with a completely filled channel. At late times, only a few large drops grow connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
184
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 16 publications
2
184
2
2
Order By: Relevance
“…They consider that these low values are due to experiments performed over a too small time interval. (They also explain the growth exponents lower than the expected value 1/3 in the initial stage [18][19][20]31,32]) by the initial transient cooling of the cold plate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They consider that these low values are due to experiments performed over a too small time interval. (They also explain the growth exponents lower than the expected value 1/3 in the initial stage [18][19][20]31,32]) by the initial transient cooling of the cold plate).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, and although this process is of major importance for the evaluation of corrosion, the studies of condensation-induced wetting on superhydrophobic surface and their corresponding wetting properties (self-cleanliness, different wetting states), are much less documented [18][19][20][21][22][23][24][25][26][27][28][29]. The aim of the present work is thus to study condensation of water on a multiscale rough superhydrophobic surface where the contact angle is varied in a wide range (70-150 • ).…”
Section: Introductionmentioning
confidence: 99%
“…Different from traditional superhydrophobic surfaces, which are characterized by the bouncing or rolling off of deposited millimeter-size large drops, [32,33] CMDSP surfaces support the self-removal capability of smallscale condensate microdrops. It has been reported that classical superhydrophobic lotus leaves (Figure 1a), [34][35][36][37] as well as artificial surfaces consisting of hierarchical micro-and nanostructures, [38] one-tier microstructures, [39][40][41][42][43] or nanostructures [44,45] with larger characteristic interspaces, present a low-adhesivity property to the deposited water macrodrops, but become highly adhesive to condensed microdrops (Figure 1b). This is because moisture easily penetrates the microscale valleys or cavities.…”
mentioning
confidence: 99%
“…Elongated drop shapes were also obtained by Chen et al [21] and Chung et al [22] for hydrophobic and hydrophilic grooved surfaces respectively. Narhe and Beysens [23] studied the growth dynamics of water drops condensing on grooved surfaces and showed that similar elongated drop shapes can be found during growth when the surface is hydrophilic, but is absent when the surface is superhydrophobic. Pakkanen and Hirvi [24] further showed that the anisotropy still persists when surface patterning is nanoscopic.…”
Section: Introductionmentioning
confidence: 99%